DIEP Flap Weights in Immediate 1-stage and 2-stage Breast Reconstruction: Considering Chest Wall Deformity - Mariko Inoue, MD; Hironobu Aoki, MD; Mina Kamegai, MD; Rei Ogawa, MD, PhD, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. There are advantages and disadvantages to both immediate 1-stage and 2-stage autologous-breast reconstruction. The 2-stage procedure may suffer from a hitherto overlooked difficulty: the tissue expander may induce chest wall depression that may require using a heavier-than-expected flap to generate symmetrical breasts. We conducted a retrospective observational study to assess this phenomenon. Methods:. Consecutive patients who underwent 1-stage or 2-stage unilateral autologous-breast reconstruction with a deep inferior epigastric perforator flap were included. The 2 groups were compared in terms of age, body mass index, mastectomized tissue weight, inset-flap weight, and percentage additional flap weight (defined as [inset-mastectomy]/mastectomy × 100). The latter reflects the amount of additional flap tissue relative to mastectomized tissue that was needed to generate symmetrical breasts. The chest wall deformity after tissue expansion in the 2-stage patients was quantitated with computed tomography. Results:. Patients’ healthy and affected breasts were symmetrical before surgery (P > 0.05). Compared with the 1-stage patients (n = 37), the 2-stage patients (n = 31) only differed in terms of a significantly higher mean percentage additional flap weight (28% versus 12%, P = 0.0077). Relative to preoperative values, nearly all 2-stage patients had mild (74%) or moderate (19%) chest wall deformity before tissue expander removal. Conclusions:. Due to tissue expander-induced chest wall deformity, 2-stage breast reconstruction may require a larger flap volume than is anticipated on the basis of preoperative volumetric measurements. Considering this phenomenon when choosing between immediate 1-stage and 2-stage reconstruction could potentially help improve patient outcomes.